PERANAN BP4 DALAM MENGENDALIKAN PERCERAIAN DI KECAMATAN SANGKAPURA PULAU BAWEAN KAB. GRESIK - Zuhri (CENDEKIA: Jurnal Studi Keislaman, 2016)
Marriage is an existing and growing institution in society. It aims to create happiness, but in its sustainability often encounter factors that sometimes hinder the creation of these objectives. Factors that hinder the achievement of happiness in marriage can break up marriages that lead to divorce. Therefore, the existence BP4 in the community is very important, even expected to remain functioning as a consultation for communities experiencing turmoil in the household, either due to a lack of inner and outer living. In practice BP4 of Sangkapura district serves as an advisory body before the parties to litigate in the Religious Court. Thus contributing of BP4 is working to make peace before the case being heard in the Religious Court. However, if a divorce case has been entered in the Religious Coutr, BP4 has almost no role at all because it is not in any divorce case BP4 asked for help and guidance. Theoretically BP4 role focused on maintaining integrity of the household and the family drove toward the couple happiness and prosperity and peace in his life. In practical terms BP4 role is to provide services to a marriage partner advisory regarding marriage and divorce disputes. The work program of BP4 of Sangkapura district actually been quite good and is expected to control the divorce and guiding families toward sakinah, mawaddah and rahmah. However, there are still shortcomings that have not been handled well, namely improving the publication widely to the public to introduce the existence and role of BP4.